giai he phuong trinh sau:\(\hept{\begin{cases}\frac{2x-3}{2y-5}=\frac{3x+1}{3y-4}\\2\left(x-3\right)-3\left(y+2\right)=-16\end{cases}}\)
giai he phuong trinh
\(\hept{\begin{cases}\frac{2x-3}{x-2}-\frac{1}{y+2}=7\\\frac{2}{x-2}-\frac{3y+7}{y+2}=13\end{cases}}\)
\(\hept{\begin{cases}x^3+y^3=9\\x^2+2y^2=x+4y\end{cases}}\)
\(\hept{\begin{cases}3x^3+5y^3-2xy=6\\2x^3+3y^3+3xy=8\end{cases}}\)
Giải hệ phương trình
\(\hept{\begin{cases}2x^2+3xy+2x+y=0\\x^2+2xy+2y^2+3x=0\end{cases}}\)
giai he phuong trinh
\(\hept{\begin{cases}x^2-4\sqrt{3x-2}+10=2y\\y^2-6\sqrt{4y-3}+11=x\end{cases}}\)
giải hệ phương trình bằng phương pháp thế
\(â,\hept{\begin{cases}3x^2+\left(6-y\right)x^2-2xy=0\\x^2-x+y=-3\end{cases}}\)
\(b,\hept{\begin{cases}x^2+y^2+xy+1=4y\\y\left(x+y\right)^2=2x^2+7y+2\end{cases}}\)
\(c,\hept{\begin{cases}x^4+2x^3y+x^2y^2=2x+9\\x^2+2xy=6x+6\end{cases}}\)
\(d,\hept{\begin{cases}x\sqrt{y+1}=1\\x^2y=y-1\end{cases}}\)
Giải hệ phương trình
\(\hept{\begin{cases}3x-4y=11\\5x-6y=20\end{cases}}\)
\(\hept{\begin{cases}\frac{2}{x}-\frac{3}{y}=1\\3x-3y=-2xy\end{cases}}\)
\(\hept{\begin{cases}2x-y=-3xy\\\frac{1}{x}+\frac{6}{y}=-1\end{cases}}\)
\(\hept{\begin{cases}\frac{3}{x+1}+\frac{1}{y+x-1}=2\\\frac{2}{x+1}-\frac{3}{y+x-1}=5\end{cases}}\)
giải các hệ phương trình sau
a) \(\hept{\begin{cases}x^2+y^2-2xy=1\\2x^2+2y^2-2xy-y=0\end{cases}}\)
b)\(\hept{\begin{cases}xy+2x-y-2=0\\xy-3x+2y=0\end{cases}}\)